Minimally invasive surgery for colorectal cancer. Initial follow-up. - Hoffman, G C (1996)
OBJECTIVE: An analysis was performed to evaluate early patterns of recurrence and survival in patients undergoing laparoscopic-assisted colectomies for primary colorectal cancer. Thirty-nine patients are available with a minimum of 24 months postoperative follow-up. SUMMARY BACKGROUND DATA: The techniques and expected surgical outcomes for patients undergoing laparoscopically assisted colectomies are slowly being defined as these procedures become more common and more widely available. One of the areas of greatest concern is the use of laparoscopic-assisted colectomy for the surgical treatment of patients with primary colorectal cancer. There are anecdotal reports in the literature describing both port site recurrence and wound recurrence in patients undergoing laparoscopic-assisted colectomies for colorectal cancer. This raises concerns about whether these recurrences are more common in patients undergoing laparoscopic procedures and whether overall survival is compromised. Wound recurrences and laparoscopic port site recurrences have been described with numerous other intra-abdominal tumors, but the precise incidence remains unknown. The authors reviewed data from 39 patients to determine early patterns of recurrence and overall survival. METHODS: Two-hundred thirty-eight laparoscopic-assisted colectomies were performed by the Norfolk Surgical Group between June 1992 and September 1995. Thirty-nine of the patients who underwent resection for colorectal cancer between June 1992 and September 1993 currently are available for at least a 2-year follow-up. Preoperative evaluation included physical examination, liver function studies, carcinoembryonic antigen, chest x-ray, computed tomography scans, and endoscopies with biopsy. Postoperative follow-up data consisted of physical examination, liver function tests, CEA, chest X-ray, computed tomography scan of the abdomen, and endoscopy of the colon. No patients have been lost to follow-up. Survival rates and patterns of recurrence were compared between node-negative and node-positive patients and compared with conventional data after open surgery. RESULTS: There were 22 men and 17 women ranging in age from 33 to 89 years. Mean follow-up was 30 months, with a range of 24 to 40 months. There were three patients with recurrence and nine deaths. Recurrence and tumor-related death rates, respectively, for each Dukes' stage were 0/1 and 0/1 for stage A, 0/7 and 0/7 for stage B-1, 1/16 and 2/16 for stage B-2, 0/1 and 0/1 for stage C-1, and 2/8 and 1/8 for Stage C-2. All six patients with Dukes' stage D disease died of metastatic colorectal cancer within 4 to 14 months of surgery. There were two patients with anastomotic recurrence. No unusual patterns of recurrent disease were noted, and there were no wound or port site recurrences. CONCLUSIONS: In this group of patients undergoing laparoscopic-assisted colectomies for primary colorectal malignancy, no adverse patterns of recurrence or decreased survival has been noted at 2-year follow-up when compared with standard open colorectal cancer surgery statistics. Prospective randomized studies with long-term follow-up will be required to better define the potential benefits and adverse effects of laparoscopic surgery for colorectal malignancy.